2015
DOI: 10.1097/mjt.0b013e3182211bae
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Prevention

Abstract: The aim of this study was to review lifestyle modification interventions and pharmacological clinical studies designed to prevent diabetes and provide evidence-based recommendations for the prevention of Diabetes Mellitus. A review of relevant literature compiled via a literature search (PUBMED) of English-language publications between 1997 and 2010 was conducted. It is found that people at increased risk of developing type 2 diabetes mellitus can halt the development of the disease. Lifestyle modification int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Prediabetes is an asymptomatic medical condition that does not cause any functional impairment; patients who are in this situation may evolve toward diabetes in varying degrees on the basis of genetic and environmental factors. Prediabetic patients are at an increased risk of developing Type 2 Diabetes Mellitus (Allende-Vigo, 2015 ). The World Health Organization estimated that 9% of adults worldwide suffer from diabetes, and the total number is predicted to increase by over 50% over the next 20 years (Fonseca, 2009 ).…”
Section: Diabetes and Related Complicationsmentioning
confidence: 99%
“…Prediabetes is an asymptomatic medical condition that does not cause any functional impairment; patients who are in this situation may evolve toward diabetes in varying degrees on the basis of genetic and environmental factors. Prediabetic patients are at an increased risk of developing Type 2 Diabetes Mellitus (Allende-Vigo, 2015 ). The World Health Organization estimated that 9% of adults worldwide suffer from diabetes, and the total number is predicted to increase by over 50% over the next 20 years (Fonseca, 2009 ).…”
Section: Diabetes and Related Complicationsmentioning
confidence: 99%
“…It has been found that metformin could lower the risk of prostate cancer, breast cancer, liver cancer, and other tumors in diabetic patients [22]. Lifestyle changes, high-sugar, high-fat diet intake, and long-term nutritional imbalance are the main causes of impaired glucose tolerance and insulin resistance [23]. Therefore, in addition to drug treatment, exercise diet intervention contributes to the control of blood sugar levels.…”
Section: Discussionmentioning
confidence: 99%
“…According to Islamic law, education can support a healthy lifestyle, diet, and life management (Halimatussakdiah et al, 2020). DM disease control and prevention can be done by implementing effective interventions through practical education (Allende-Vigo, 2015;Nguyen et al, 2016). Prevention of NCDs, it is necessary to develop an intervention program to reduce the number of NCDs in the community with accessible education (Kufe et al, 2016).…”
Section: The Effect Of the Syar'i Video On Dm Preventionmentioning
confidence: 99%